A STUDY ON THE DEMOGRAPHICAL STRUCTURE OF PRE-MODERN TIMES IN SRI LANKA (History Department, Semarang State University and Historian Society of Indonesia, 2018)
The core of this study is to examine the scientific community structure of the pre-modern era of the Sri Lankan society. While this study will be focused only on the migration of people of the Indian and South–East Asian origins to the Western and South-Western regions of Sri Lanka during the specified time period, how the influence of those migrations was reflected on the Sri Lankan architecture of the same period will also be examined. The simultaneous decline of the Rajarata Civilization that lasted for thousands of years uninterrupted and the acceleration of settlements in the Western and the South-Western regions of Sri Lanka in the 13th century was an outcome of the people who left Rajarata fearing the invasion of the Kalinga Magha, one of the reasons behind the discontinuation of the Rajarate Administrative System, as well as some regional leaders in Maya and Rohana not supporting the Magha and acting as independent leaders. Inti dari penelitian ini adalah untuk memeriksa struktur komunitas ilmiah dari era pra-modern masyarakat Sri Lanka. Meskipun studi ini hanya akan difokuskan pada migrasi penduduk India dan Asia Tenggara ke daerah Barat dan Selatan-Barat Sri Lanka selama periode waktu tertentu, bagaimana pengaruh migrasi tersebut tercermin pada Sri Lanka. Arsitektur periode yang sama juga akan diperiksa. Kemunduran simultan Peradaban Rajarata yang berlangsung selama ribuan tahun tanpa gangguan dan percepatan pemukiman di wilayah Barat dan Selatan-Barat Sri Lanka pada abad ke-13 adalah hasil dari orang-orang yang meninggalkan Rajarata karena takut akan invasi Kalinga. Magha, salah satu alasan di balik penghentian Sistem Administrasi Rajarate, serta beberapa pemimpin regional di Maya dan Rohana tidak mendukung Magha dan bertindak sebagai pemimpin independen.